Estimation of 24-Hour Urinary Sodium Excretion Using Spot Urine Samples - Rhee, Moo-Yong; Kim, Ji-Hyun; Shin, Sung-Joon; Gu, Namyi; Nah, Deuk-Young; Hong, Kyung-Soon; Cho, Eun-Joo; Sung, Ki-Chul (Nutrients, 2014)
The present study evaluated the reliability of equations using spot urine (SU) samples in the estimation of 24-hour urine sodium excretion (24-HUNa). Equations estimating 24-HUNa from SU samples were derived from first-morning SU of 101 participants (52.4 ± 11.1 years, range 24–70 years). Equations developed by us and other investigators were validated with SU samples from a separate group of participants (n = 224, 51.0 ± 10.9 years, range 24–70 years). Linear, quadratic, and cubic equations were derived from first-morning SU samples because these samples had a sodium/creatinine ratio having the highest correlation coefficient for 24-HUNa/creatinine ratio (r = 0.728, p < 0.001). In the validation group, the estimated 24-HUNa showed significant correlations with measured 24-HUNa values. The estimated 24-HUNa by the linear, quadratic, and cubic equations developed from our study were not significantly different from measured 24-HUNa, while estimated 24-HUNa by previously developed equations were significantly different from measured 24-HUNa values. The limits of agreement between measured and estimated 24-HUNa by six equations exceeded 100 mmol/24-hour in the Bland-Altman analysis. All equations showed a tendency of under- or over-estimation of 24-HUNa, depending on the level of measured 24-HUNa. Estimation of 24-HUNa from single SU by equations as tested in the present study was found to be inadequate for the estimation of an individual’s 24-HUNa.